2021
DOI: 10.1186/s13071-021-04862-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and biological characterization of Cryptosporidium muris from camels (Camelus bactrianus) in China

Abstract: Background Cryptosporidium is an opportunistic pathogen that infects a wide variety of vertebrates. The aim of the present study was to characterize Cryptosporidium spp. isolates from Bactrian camels and to foster further understanding of the biological characteristics of the pathogen. Methods Fecal specimens were collected from two 4-year-old Bactrian camels resident at the Kaifeng City Zoo in China and examined for Cryptosporidium. Fecal specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…Conversely, significantly increased ACE index ( P < 0.01) and Chao index ( P < 0.01) at 14 days after C. muris infection indicated that the fecal-microbiota richness was increased during this period. Overall, these data suggested that mice infected with C. muris had higher microbiota richness at the peak of oocysts shedding (14 dpi) ( 5 ). β-Diversity analysis was used to confirm the differences and similarities in gut microbial community composition between groups.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Conversely, significantly increased ACE index ( P < 0.01) and Chao index ( P < 0.01) at 14 days after C. muris infection indicated that the fecal-microbiota richness was increased during this period. Overall, these data suggested that mice infected with C. muris had higher microbiota richness at the peak of oocysts shedding (14 dpi) ( 5 ). β-Diversity analysis was used to confirm the differences and similarities in gut microbial community composition between groups.…”
Section: Resultsmentioning
confidence: 93%
“…Bacteria such as Lachnospiraceae and Desulfovibrionaceae increased in abundance during C. muris infection, especially at 14 dpi. Interestingly, previous studies have shown that the number of shed oocysts peaks on the second week after C. muris infection in mice ( 5 , 21 ). Lachnospiraceae contribute toward to pyruvate metabolism to drive SCFA biosynthesis ( 22 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Cryptosporidium muris , a gastric species, has a very wide host range including rodents, ruminants, cats and dogs, horses, Bactrian camels, pigs, birds, and non-human primates [ 22 , 23 , 40 , 162 , 194 , 195 , 196 , 197 , 198 ]. There have been numerous reports in humans, particularly in developing countries (in children and HIV patients) [ 1 , 5 ], ( Table 1 ).…”
Section: Zoonotic Cryptosporidium Species and Genotypesmentioning
confidence: 99%
“…Light microscopic examination of C. parvum-infected gastric sections showed desquamation of the gastric glands' epithelium associated with the presence of oocysts within the epithelial lining and within the lumen of the gastric glands as well as marked hyperplastic changes within the mucus cells [33]. Concerning the gastric sections of the infected MTZ, garlic, ginger, and pomegranate-treated mice, they retrieved their normal structure-like healthy noninfected mice.…”
Section: Discussionmentioning
confidence: 98%